Thoracic Outlet Syndrome Case Report: Appropriate Diagnosis Can Expedite Patient Treatment and Prevent Negative Outcomes - Hunter Triplett; Victoria Winter; Brandon Leary; Alexis Lee; Kathryn Sulkowski; Eugene Kang (Clinical Practice and Cases in Emergency Medicine)
Introduction: Thoracic outlet syndrome (TOS) is a diagnosis classifying upper extremity symptoms caused by compression of the neurogenic and vascular structures between the clavicle and first rib. It is important to promptly decompress these structures to prevent long-term deficits and poor patient outcomes. However, TOS often presents in unique ways with substantial symptom variance, making it difficult to identify, diagnose, and promptly treat. Compounding this, common diagnostic tools such as magnetic resonance imaging are not independently appropriate for a conclusive diagnosis of TOS. Patients with TOS can initially present acutely due to symptom exacerbations or emergent situations, necessitating multimodal diagnostic methods and early TOS recognition to improve patient outcomes, particularly in emergency department (ED) settings. Case Report: A 22-year-old male presented with chronic symptoms of numbness and weakness in his right hand in addition to chest pain that radiated into his right elbow, along with a diminished right radial pulse. The patient also suffered from acute symptomatic exacerbations of total arm asthenia, paresthesia, and what the patient described as “an intensely cold hand” during football practice. He was eventually treated with a right first-rib resection to decompress the brachial plexus, which resulted in complete symptom resolution and recovery. Conclusion: Due to the serious long-term complications associated with uncorrected brachial plexus compression and the fact that TOS patients can initially present to ED settings with acute exacerbations, it is important for emergency clinicians to be able to recognize and either treat or appropriately refer patients for treatment. The ED is equipped to enable physicians to perform a comprehensive diagnostic assessment because they often have access to the diagnostic modalities necessary for diagnosing thoracic outlet syndrome.